Assessment of heavy metal traces (Copper and lead) in the soft tissue of oysters Crassostrea virginica. - Balboa, Dexter Gicaro
The bivalve mollusk Crassostrea virginica is abundant in Brgy. Calaparan, Arevalo and Brgy. Bacong, Dumangas; and are widely consumed by the residence as food. Bioaccumulation of Copper and Lead in the soft tissues of C. virginica from Brgy. Calaparan, Arevalo and Brgy. Bacong, Dumangas were measured and checked if they are still within the permissible levels of copper and Lead in food based on Median International Standards for metals compiled by the Food Agricultural Organization of the United nations. Metal concentrations (ug/g) were determined using Flame Atomic Absorption Spectrophotometer. Mean concentrations of the heavy metals in C. virginica from Calaparan, Arevalo - Cu 27.829, Pb 1.2133; Bacong, Dumangas- Cu 57.834, Pb 0.1338. These levels of copper and Lead in oyster tissue from both sites are within the range of Median International Standards for metals and are safe for human consumption. Statistical analysis through one-way ANOVA ( > F Ferit, showed significant difference between sites (Ferit = 18.51282) for Copper (F value, 215.06569) but not for Lead (F value, 2.25151). The study also provided further soled evidence that bivalve like Crassostrea virginica can recover and concentrate environmentally derived and anthropogenic traces of heavy metals.